PEMELIHARAAN KESEHATAN GIGI MULUT DAN ORAL HYGIENE IBU HAMIL DI WILAYAH KERJA PUSKESMAS BARA BARAYYA KOTA MAKASSAR - Alfah, Siti; AR, Aisyah; Nurhaedah, Nurhaedah; Hikmah, Nurul; Hidayat, Rahmat (Jurnal Ilmiah Amanah Akademika, 2021)
Background: Hormonal changes in pregnant women cause various complaints such as cravings, nausea, vomiting including complaints of toothache as a result of the habit of ignoring dental and oral hygiene. Changes in eating patterns and habits of not maintaining oral hygiene due to feelings of lethargy, nausea and vomiting in some pregnant women can increase the risk of dental and oral diseases which in their development will affect the condition of their pregnancy. Objective: To determine the maintenance of oral health and oral hygiene of pregnant women in the working area of the Bara Barayya health center. Method: This type of research is descriptive with a sample size of 124 people taken using simple random sampling. The research was conducted in the working area of the Bara Barayya Community Health Center. Data collection was carried out by distributing questionnaires to determine the actions of pregnant women in maintaining oral hygiene, as well as examining the oral hygiene of pregnant women based on the Oral Hygiene Index (OHIS-S). Results: The results of the study show that dental and oral health maintenance measures for pregnant women in the working area of the Bara Barayya health center are classified as good with Oral Hygiene with moderate criteria. Conclusion: Based on research on 124 pregnant women in the working area of the Bara Barayya Community Health Center, it can be concluded that most of the dental and oral health maintenance actions of pregnant women are in the good category.